Exploring microbial diversity of marine sponges by culture-dependent and molecular approach - Mohamad, Mohd Azrul Naim (Wageningen University, 2015)
Discovery of sponge-grade metazoans dated 650 million years ago proved that sponges have been around since the Precambrian era. Their resilience to ever-changing environmental conditions and their global distribution is one of the features attributed to the symbionts in sponges, which include Archaea, Bacteria and Eukarya. It is yet unknown how sponges attract and select their bacterial associates but mechanisms to maintain or newly acquire their symbionts have been demonstrated, such as vertical and horizontal transmission. Discovery of species-specific bacterial communities in the marine sponges H. panicea, H. oculata and H. xena which are dominated by an alpha, beta- and gammaproteobacterium, respectively, confirmed host-specificity of bacterial associates in marine sponges from the North Sea, although their function remains unknown. Detection of Chlamydiae in high relative abundance raised the question as to what is their function in the sponge holobiont as they were only distantly related to other known Chlamydiae. Little is known about the fungal community in marine sponges. This prompted the study of sponge-associated fungi based on molecular analysis. This was previously a difficult enterprise due the large amount of ‘contaminating’ sponge DNA, which is susceptible to amplification with fungi-specific PCR primers as well. The advent of next generation sequencing technology now for the first time allowed to overcome this hurdle by the sheer numbers of sequences that can be generated. This lead to discovery of novel yeast lineages from the phyla Ascomycota and Basidiomycota in North Sea and Mediterranean marine sponges, indicating a much higher diversity of fungi yet to be explored. For instance, yeasts from the order Malasseziales, which are common pathogens of marine animals, were found as the dominant yeasts in many of the sponges tested that were without apparent disease. A complementary cultivation-dependent approach provided access to fungal isolates. Fungi belonging to the genus Penicillium were found to be the dominant fungi recovered by isolation from the Mediterranean sponges Aplysina aerophoba, Petrosia ficiformis and Corticium candelabrum. In addition, fungi belonging to the order Alternaria and yeasts affiliated to the genus Rhodotorula were isolated multiple times. No overlap was found with the fungal species observed through the molecular study, which indicates that the great plate anomaly also exists for fungi. Many of the fungal Pencilillium and Alternaria strains isolated were shown to have the genetic capacity for producing polyketide synthases (PKS) or PKS-non ribosomal peptide synthase (PKS-NRPS) hybrids. These enzyme complexes are generally responsible for the production of secondary metabolites with a high biological activity. Isolation of bacteria from H. panicea in a cultivation experiment with a large diversification of media and growth conditions and subsequent comparison of the retrieved microorganisms to bacteria found in the sponge tissue by a molecular approach revealed the presence of bacterial genera that dominate the cultivation library, but comprise of represent minor components of the sponge microbiome. This includes genera such as Bacillus, Paracoccus and Shewanella. Another genus that was commonly isolated from many marine sponges, but only is found at low relative abundance in the sponge microbiome is Pseudovibrio. Phenotypic characterization based on antibiotic resistance and genotypic differentiation based on bacterial BOX elements and presence of halogenase-encoding genes could discriminate closely related strains that could not be distinguished based on their 16 rRNA gene sequence. In conclusion, this thesis helps to bridge the gap between cultivation-dependent and cultivation-independent studies of sponge-associated bacteria and fungi by clearly defining the frontiers of the gap. The knowledge derived from this thesis could serve as a scientific foundation and inspiration for future microbial diversity studies and provides perspective for analysing and exploiting sponge symbionts.